Human Adenovirus B7d–Associated Urethritis after Suspected Sexual Transmission, Japan - Hanaoka, Nozomu; Ito, Shin; Nojiri, Naomi; Konagaya, Masami; Yasuda, Mitsuru; Deguchi, Takashi; Fujimoto, Tsuguto (Emerging infectious diseases, 2020)
Outbreaks of acute respiratory disease associated with human adenovirus (HAdV) B7d have been reported, including fatal cases in the United States. In 2018, we detected HAdV-B7d in a patient with urethritis, probably transmitted through sexual contact. Infectious HAdV-B7d was excreted in urine and gargle for >10 days after the disappearance of symptoms.